TINDAK PIDANA PENISTAAN AGAMA DALAM RANCANGAN UNDANG-UNDANG KITAB UNDANG-UNDANG HUKUM PIDANA NASIONAL - Soewondo, Suharto (Universitas Wiralodra, 2013)
Constitution of the Republic of Indonesia as well as the constitutional anvil or Grundnorm or basic rules of the Republic of Indonesia governing the freedom of every citizen to adopt a religion or belief of each corresponding confidence of the citizens themselves , the problem arises when there is a person or group of people , organizations that commit crimes against religion which is often called the desecration / blasphemy . Blasphemy actually being governed by Article 156a of the Penal Code , but the rampant criminal offense of blasphemy as many cult in Indonesia and law enforcement are less strict fueled the Draft Law Code of Criminal Law ( Draft Bill ) which is the view of the author suggests that religion does not deserve to be protected by anyone , including the state , but which needs to be protected is the religious affiliation or belief itself , of course, when there is an offense against the blasphemy to get strict sanctions that punishment / sorrow